2019
DOI: 10.1186/s12879-019-4453-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Cryptococcus infections as a manifestation of idiopathic CD4 lymphocytopenia: case report and literature review

Abstract: Background Idiopathic CD4 lymphocytopenia (ICL) is a rare clinical disease with relative CD4 deficiency in the absence of HIV infection. The pathogenicity of ICL is poorly understood with an unclear incidence rate in the general population. Sequelae of ICL includes AIDS-defining infections, which most commonly includes Cryptococcus neoformans. Typically, C. neoformans infections present with CNS involvement but rarely with extra-CNS manifestations. Here, we present a rare case of ICL with exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A Th1-Th17 cytokine profile is associated with increased phagocytic activity and inhibition of the growth of Cryptococcus [7]. Our previous study revealed that patients with CD4 T lymphocyte cell counts greater than 378/µL were more likely to be asymptomatic and had a lower mortality rate than those with lower CD4+ T lymphocyte counts [8,9]. Similarly, another study confirmed that patients with CD4+ T lymphocyte counts lower than 400/μL were prone to disseminated cryptococcosis [10].…”
Section: Introductionmentioning
confidence: 94%
“…A Th1-Th17 cytokine profile is associated with increased phagocytic activity and inhibition of the growth of Cryptococcus [7]. Our previous study revealed that patients with CD4 T lymphocyte cell counts greater than 378/µL were more likely to be asymptomatic and had a lower mortality rate than those with lower CD4+ T lymphocyte counts [8,9]. Similarly, another study confirmed that patients with CD4+ T lymphocyte counts lower than 400/μL were prone to disseminated cryptococcosis [10].…”
Section: Introductionmentioning
confidence: 94%
“…Only few studies on PC have focused on the correlation between CT findings and CD4 cell count or HIV viral load in immunocompromised patients, and most of these studies are case reports or have a small sample size (10,11). On the other hand, the majority of studies with a larger sample size have concentrated on the clinical and imaging characteristics of Cryptococcus in different immune states (3,12) or have simply compared the clinical and imaging features of immunocompetent and immunocompromised patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Regent et al found cryptococcal infection (26.7%) as the most common opportunistic infection followed by mycobacterial infection (17%) and histoplasmosis (3.1%) in ICL [14]. Subsequently, around 66 more cases were reported till 2020 in the literature [15]. Among them, a cases series of 40 patients showed that opportunistic infections were present in 62.5% of ICL cases (human papilloma virus, cryptococcus meningitis, pneumocystis pneumonia and mycobacterial tuberculosis were most common infections) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, around 66 more cases were reported till 2020 in the literature [15]. Among them, a cases series of 40 patients showed that opportunistic infections were present in 62.5% of ICL cases (human papilloma virus, cryptococcus meningitis, pneumocystis pneumonia and mycobacterial tuberculosis were most common infections) [15]. The association of histoplasmosis and ICL is rare and CD4 count was not done in all reported immunocompetent cases.…”
Section: Discussionmentioning
confidence: 99%